2004
DOI: 10.1002/eji.200425368
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal stimulation of γδ T cells and dendritic cells during the anti‐mycobacterial immune response

Abstract: cd Tcells and dendritic cells (DC) are two distinct cell types of innate immunity that participate in early phases of immune response against Mycobacterium tuberculosis infection. Here we show that a close functional relationship exists between these cell populations. Using an in vitro coculture system, Vc1 T cells from Tcrb -/-mice were found to be activated by DC infected in vitro with BCG, as indicated by the elevated CD69 expression, IFN-c secretion and cytotoxic activity. This activation process was due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 36 publications
1
55
1
Order By: Relevance
“…Our previous in vitro studies showed that cd T cells significantly influence the development of antigen-specific cytotoxic CD8 T cells, and this effect seems to be mediated by DC. These cellular interactions suggest that cd T cells might help to control mycobacterial infection in the transition period between innate and CD8 T cell-mediated adaptive immunity [17]. These in vitro studies have been expanded in this paper to in vivo conditions, using Tcrd -/-mice.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Our previous in vitro studies showed that cd T cells significantly influence the development of antigen-specific cytotoxic CD8 T cells, and this effect seems to be mediated by DC. These cellular interactions suggest that cd T cells might help to control mycobacterial infection in the transition period between innate and CD8 T cell-mediated adaptive immunity [17]. These in vitro studies have been expanded in this paper to in vivo conditions, using Tcrd -/-mice.…”
Section: Resultsmentioning
confidence: 95%
“…This non-cognate interaction conditions DC for effective priming of anti-mycobacterial CD8 T cell responses [17]. We therefore asked whether cd T cells influence the activity of lung DC in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…are also involved in cd T-cell activation. 23,25,[51][52][53][54] Moens and colleagues showed that human neonatal DC-derived IL-23 combined with specific TCR signaling drives the generation of neonatal Vc9Vd2 T cells equipped with a range of cytotoxic mediators and distinct subpopulations producing IFN-c and IL-17. Dimova and colleagues revealed that the immune response after bacillus Calmette-Guérin vaccination of infants can drive cd T cells into an effector cell type that produce IFN-c and mediate cytotoxicity.…”
Section: Function In Infectious Diseasesmentioning
confidence: 99%